MEMAHAMI AGAMA DAN BUDAYA SEBAGAI SOLUSI MENGATASI KONFLIK TEOLOGIS - A. Zaini Dahlan (CMES (Center of Middle Eastern Studies), 2015)
This article is intended to establish a common perception in the understanding of religion as a way of life or common life rule in religion and nation. Therefore in this article described the essence of religious term that is misunderstood by some people - the negative effects of ignorance about the essence and incomprehension about the various terms of religion - is the extreme attitude in religious life, that's so convicting others (who do not agree with him) as an "infidel", "the lost", even worse  they take anarchy action to "justify the blood" of others for the same reason. Besides, to avoid the "negative effects" above, this article also aims to realize and prove that Islam is a friendly, polite, tolerant religion - as did the prophet in Medina charter- more particularly the diversity (diversity - which is the grace of the gods- as proof that Islam brings blessing for the whole world (rahmatan lil 'alamin).